Fourier Series Approximation in Besov Spaces - Birendra Singh; Uaday Singh (Journal of Mathematics)
Defined on the top of classical Lp-spaces, the Besov spaces of periodic functions are good at encoding the smoothness properties of their elements. These spaces are also characterized in terms of summability conditions on the coefficients in trigonometric series expansions of their elements. In this paper, we study the approximation properties of 2π-periodic functions in a Besov space under a norm involving the seminorm associated with the space. To achieve our results, we use a summability method presented by a lower triangular matrix with monotonic rows.